Student research poster - from processing-in-Memory to Processing-in-Storage - Kaplan, Roman (2016 International Conference on Parallel Architecture and Compilation Techniques (PACT), 2016)
This paper studied a new technology and approach - Processing-in-Storage (PrinS). Resistive technologies have shown high-density, high-endurance and low energy. Such features might provide the conditions for a petascale storage device, where each cell has both storage and processing capabilities. There are numerous research directions in studying the approach, to list a few: building peripheral circuitry to support multiple types of computations, maintaining low latency for data access, providing high-throughput processing, ease of programmability, etc.